Analisis Strategi Pemasaran dalam Meningkatkan Volume Penjualan pada Pangkalan Gas "Rezfa" Depok - Wijaya, Bagas Aji; Oktaviani, Reza (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research aims to determine the marketing strategy carried out by the REZFA LPG gas base in increasing sales volume. In this research, a qualitative approach was used. Data collection in this research was carried out using triangulation, namely interviews, direct observation and documentation. The data analysis technique used in this research is the stages of data collection, data reduction, data presentation and drawing conclusions and verification and entered in the Triangulation table to conclude information about the same thing obtained from various parties. The results of this research indicate that REZFA LPG gas base has implemented a marketing strategy, namely market segmentation, market targeting, market positioning and a good and appropriate marketing mix strategy for product, price, location, promotion, physical evidence, human resources, processes (7P). However, there are still marketing strategies that must be developed further, such as promotional strategies so that the sales volume of the REZFA LPG gas base can increase to obtain appropriate profits so that base growth is not hampered due to lack of funds.